2016
DOI: 10.1186/s40781-016-0102-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of feeding mixed microbial culture fortified with trace minerals on ruminal fermentation, nutrient digestibility, nitrogen and trace mineral balance in Sheep

Abstract: BackgroundThe aim of the present study was to determine the effects of feeding trace mineralsfortified mixed microbial culture (TMC) on ruminal fermentation, nutrient digestibility, blood electrolyte status, nitrogen balance, and trace mineral balance in sheep.MethodsMixed microbes [0.6 % (v/w) of Enterobacter sp., Bacillus sp., Lactobacillus sp., and Saccharomyces sp.] were cultured with 99 % feedstuffs and 0.4 % trace minerals including zinc and copper for ensiling. Six sheep (a mean body weight of 46.5 ± 1.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 37 publications
1
9
0
Order By: Relevance
“…Salama et al (2003) showed that Zn supplementation increased digestibility of DM and OM of goats. However, Kwak et al (2016) and Pino and Heinrichs (2016) found that the digestion coefficients of DM, OM, CP, EE, CF and NFE% were not affected by additives of trace minerals. The obtained data showed that TDN values were significantly increased with mineral additives of the goat in both experiments.…”
Section: Discussionmentioning
confidence: 93%
See 4 more Smart Citations
“…Salama et al (2003) showed that Zn supplementation increased digestibility of DM and OM of goats. However, Kwak et al (2016) and Pino and Heinrichs (2016) found that the digestion coefficients of DM, OM, CP, EE, CF and NFE% were not affected by additives of trace minerals. The obtained data showed that TDN values were significantly increased with mineral additives of the goat in both experiments.…”
Section: Discussionmentioning
confidence: 93%
“…The NH3-N values were significantly higher at 2 h and 4 h than 0 h in sheep and goats. Qi et al (1992), Fathul and Wajizah (2010) and Kwak et al (2016) found that mineral additives did not affect ruminal NH 3 -N. However, Xun et al (2012) found that ruminal ammonia N was significantly decreased with Se supplementation. In this study, the increasing in NH 3 -N in the experiment 2 than the experiment 1 may be due to the high percent of protein in alfalfa consumed by animals in the experiment 2.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations